Pengaruh Struktur Kepemilikan Perusahaan Terhadap Nilai Perusahaan Yang Dimediasi Oleh Pengungkapan Environmental, Social, and Governance (ESG) Pada Perusahaan IDX80 Periode 2019-2023 - Putri, Viano Mercy; Taurusianingsih, Dyah Nirmalawati (Jurnal Ecogen, 2025)
This study aims to examine the impact of ownership structure on firm value, with the disclosure of Environmental, Social, and Governance (ESG) activities serving as a mediating variable. The analysis is conducted on a sample of 90 companies listed in the IDX80 index on the Indonesia Stock Exchange over the period 2019 to 2023. Using panel regression analysis and the Sobel test to assess the mediating effect, the results reveal that institutional and managerial ownership have a positive and significant influence on firm value, both directly and indirectly through ESG disclosure. In contrast, family ownership has a negative effect on ESG disclosure. Furthermore, ESG disclosure itself has a significant positive effect on firm value. The findings underscore the strategic role of ESG as a transmission mechanism that strengthens the relationship between ownership governance and value creation. The study contributes to the agency theory by demonstrating how different types of ownership can influence managerial incentives and disclosure practices, ultimately affecting firm valuation. These results offer meaningful implications for corporate decision-makers and investors, highlighting the importance of ownership structure and sustainability practices in improving market performance.